Addressing Bibliphobia Amongst Primary School Pupils In Ilorin Metropolis - Oreagba, Fatimah; Lasisi, Adekola Kamil (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2024)
Bibliophobia, the fear of books, is a pervasive issue that significantly hinders academic achievement and lifelong learning, particularly among primary school pupils. This position paper analyzes the phenomenon of bibliophobia within the context of the Ilorin Metropolis, arguing that it is a multifaceted issue shaped by sociocultural, psychological, and educational factors. Utilizing a comprehensive literature review and theoretical frameworks, the paper identifies key influences contributing to bibliophobia, such as family dynamics, educational practices, and societal attitudes toward reading. The research methodology focuses on synthesizing existing studies and theoretical perspectives to illuminate the complexities of bibliophobia. Through thematic analysis, the paper reveals critical insights regarding the need for a multifaceted approach to address this issue. It underscores the importance of parental engagement, teacher training, and effective guidance and counselling strategies in fostering a positive reading environment. The findings call for targeted policy interventions aimed at instilling a love of reading among primary school pupils and reducing the prevalence of bibliophobia. By engaging stakeholders—parents, educators, and policymakers—this paper seeks to stimulate dialogue and awareness surrounding bibliophobia, ultimately contributing to improved educational outcomes. In conclusion, addressing bibliophobia through collaborative efforts and informed strategies is essential for promoting literacy and enhancing the overall learning experience for children in Ilorin Metropolis.